Pengaruh Dukungan Relasional dan Dukungan Pendidikan terhadap Minat Berwirausaha Mahasiswa - Lyly Sajidah Bestari; Mintasih Indriayu; Aniek Hindrayani (Universitas Negeri Surabaya, 2023)
This study aimed to determine the effect of relational support and educational support on the interest in entrepreneurship for undergraduate students of Sebelas Maret University. This research was a quantitative descriptive study with a population of 24,753 students for the 2020/2021 academic year. The sampling technique used in this study was proportionate stratified random sampling, producing a sample of 394 student respondents. Data was collected through a questionnaire distributed via the Google form link. The data analysis used was multiple linear regression analysis with SPSS 25. The results shown from this study were: First, relational support had a positive and significant effect on the interest in entrepreneurship of undergraduate students of Sebelas Maret University. Second, educational support had a positive effect and significant on the interest in entrepreneurship for undergraduate students of Sebelas Maret University. Third, relational support and educational support simultaneously had a positive effect and significant on the interest in entrepreneurship of undergraduate students of Sebelas Maret University.